Intelligent Quranic ontology retrieval - Nurlida Basir; Nur Fatin Nabila Mohd Rafei Heng; Madihah Mohd Saudi; Farida Hazwani Mohd Ridzuan; Sakinah Ali Pitchay; Zaizi N.J.M. (American Scientific Publishers, 2024)
Indexed by Scopus